Prevalence, characteristics, and predictors of pre-diabetes in Indonesia (Medical Journal of Indonesia, 2011)
Background: Pre-diabetes is a state where glucose level higher than normal, but not satisfy the criteria for diabetes. This condition is very critical, so that if subject don't do lifestyle modification and pharmacology therapy, they could fall to diabetes. This research objective is to describe the prevalence and predictors of pre-diabetes in Indonesia. Methods: A cross-sectional study was conducted by Metabolic Endocrinology Division, Department of Internal Medicine FMUI/RSCM and Jakarta Diabetes and Lipid Center using secondary data from National Health Survey 2007. Total respondents are 24417 subjects from 33 provinces in Indonesia. We analyze characteristics, correlation, predictors, and attributable risks for some predictors of pre-diabetes and diabetes. Results: Prevalence of pre-diabetes (based on impaired glucose tolerance data) in Indonesia is 10%. Predictors of pre-diabetes are male, old-age, high socio-economic status, low education level, hypertension, obesity, central obesity, and smoking. Priority for pre-diabetes and diabetes prevention in Indonesia directed to decrease blood pressure (Attributable Risk/AR 56.5%), reduce waist circumference (AR 47.3%), and stop smoking (AR 44.4%). Conclusion: Prevalence of pre-diabetes in Indonesia is high so that we need a prevention strategy for pre-diabetes and the development from pre-diabetes to diabetes. The implementation of those strategies is compiled in the Indonesian Diabetes Prevention Program.(Med J Indones 2011; 20:283-94)